Les enjeux érosifs dans le vignoble patrimonial à fortes pentes de Banyuls-sur-Mer (France) - Eric Rouvellac; Fabien Cerbelaud; Rémi Crouzevialle; Véronique Maleval (Belgeo)
In the Banyuls-sur-Mer vineyard, in the Alberes mountains in the eastern Pyrenees, the very steep slopes and Mediterranean precipitations lead to severe erosion which has preoccupied winegrowers for centuries. Methodologically, using very high-resolution digital terrain models, georeferenced by centimetric precision GNSS positions, and using a drone to build them, we can measure the amount of soil eroded between two missions, and compare them with precipitations. From two test areas arranged differently to erosion, we were able to make initial calculations and compare them to old empirical studies.